Pengaruh Safety Leadership terhadap Safety Behaviour di Industri Manufaktur Perkeretaapian - Melia Chandra Millana; Lukman Handoko; Farizi Rachman; Novita Anggraini (Journal of Safety, Health, and Environmental Engineering, 2024)
The railroad manufacturing industry continues improving all aspects to support business processes. The increase that occurred was accompanied by an increase in work accidents as well. By changing the mindset of individuals into a new paradigm that is focused on safety behavior, it is able to improve the OHS culture. Through implementing and improving safety behavior, it is hoped that it will be able to form K3 cultured workers. This study aims to analyze the effect of safety leadership (safety motivation, safety concern, and safety policy) on safety behavior (safety compliance and safety participation). The measurement instrument for this study was to use a questionnaire with a total of 128 workers as respondents. The research questionnaire uses a Likert scale of 1 (strongly disagree) – 4 (strongly agree). The results of the primary data were then processed and analyzed using multiple linear regression methods with the help of statistical data processing software. Before carrying out multiple linear regression analysis, validity and reliability tests were carried out using a random sample of 50 respondents. After it was found that the instrument was valid and reliable, then multiple linear regression was performed starting with the classical assumption test, simultaneous significance test (F test), and individual parameter significance test (T test). Furthermore, the results of multiple linear regression analysis showed that all variables from safety leadership have an effect on safety compliance. Based on the data, the p-value results were obtained for safety motivation (0.047), safety concern (0.000), dan safety policy (0.000). Meanwhile, there are only two variables from safety leadership that influence safety participation, with p-values on safety motivation (0.043), safety concern (0.002), dan safety policy (0.000).